2013
DOI: 10.4236/ajps.2013.45a005
|View full text |Cite
|
Sign up to set email alerts
|

Seeds as a Source of Carbon, Nitrogen, and Phosphorus for Seedling Establishment in Temperate Regions: A Synthesis

Abstract: Seeds are a source of organic (carbon, C) and mineral (nitrogen, N and phosphorus, P) nutrients for the growing seedling. There is much information on seed mass and N and P contents, and the relationship between these and seedling mass. Within the world's temperate regions, these collectively show that N and P concentrations remain constant or rise with increase in seed mass and that seeds are larger and more nutrient-enriched in poorer soils. Seed N and P were more important than seed C in accounting for seed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
44
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 61 publications
3
44
0
1
Order By: Relevance
“…Initial growth by recently germinated seedlings is linked to seed size in many species, with large seeds producing larger seedlings than small seeds (Marshall 1986;Jurado and Westoby 1992;Osunkoya et al 1993;Leishman and Westoby 1994). In particular, cotyledon reserves of carbon, nitrogen and phosphorus are critical for the early vegetative growth of Banksia seedlings in water-limited and nutrient-poor environments (Groom et al 2001;Lamont and Groom 2013). In this study, it was found that Banksia attenuata has seeds five times larger and seedlings (3 months old) twice as large as B. littoralis.…”
Section: Discussionmentioning
confidence: 98%
“…Initial growth by recently germinated seedlings is linked to seed size in many species, with large seeds producing larger seedlings than small seeds (Marshall 1986;Jurado and Westoby 1992;Osunkoya et al 1993;Leishman and Westoby 1994). In particular, cotyledon reserves of carbon, nitrogen and phosphorus are critical for the early vegetative growth of Banksia seedlings in water-limited and nutrient-poor environments (Groom et al 2001;Lamont and Groom 2013). In this study, it was found that Banksia attenuata has seeds five times larger and seedlings (3 months old) twice as large as B. littoralis.…”
Section: Discussionmentioning
confidence: 98%
“…Phosphorus is a key mineral nutrient in every plant process that involves energy transfer, and developing seeds are the main source of phosphorus during plant growth. Lamont and Groom (2013) indicated that young plants developed from large, nutrient-enriched seeds were more protected against drought compared to seedlings sprouted from the smaller seeds. This is because the substantial amounts of phosphorus and nitrogen in large seeds play a critical role in photosynthesis, ensuring sufficient carbon delivery to the rapidly descending roots for effective drought-avoidance.…”
Section: Discussionmentioning
confidence: 99%
“…Proteaceae of the CFR show high functional diversity and are model organisms for ecological research (Schurr, Esler, Slingsby, & Allsopp, 2012). Within the global spectrum of plant functional traits, Proteaceae species exhibit conservative nutrient use and reproduce from relatively large, nutrient-rich seeds (DĂ­az et al, 2016;Lamont & Groom, 2013).…”
Section: Study Region and Study Speciesmentioning
confidence: 99%
“…Although Westoby's (1998) leaf-height-seed (LHS) scheme provides a preliminary shortlist of trait spectra [specific leaf area (SLA), plant height and seed mass], other traits may also describe plant responses to competition, environmental stress and disturbance (reviewed by Westoby & Wright, 2006). In contrast, responses to disturbance, such as fire, depend on architectural traits and resprouting ability (Clarke et al, 2013), as well as seed traits (Lamont & Groom, 2013). In contrast, responses to disturbance, such as fire, depend on architectural traits and resprouting ability (Clarke et al, 2013), as well as seed traits (Lamont & Groom, 2013).…”
Section: Introductionmentioning
confidence: 99%